Impact of microjets on the flow of a duct. (2022) - Afghan Khan, Sher; Suheel, J.I.; Ridwan,; Mokashi, Imran; Kumar, Arvind; Faheem, Mohammed
Abstract: This study investigates the streaming development in the tube and pressure recovery once the flow regulator is activated in the recirculation zone at a different level of expansions. The Mach numbers considered are 1.87, 2.2, 2.58. The duct diameter is 16 mm. Tiny jets of 1 mm diameter are placed at the midplane of the base to regulate the flow. The control jet's Mach number is unity as they are circular orifice despite the NPR of the control jet being very high. The investigations reveal that the stream remained connected with the duct even for L = 1D for the entire Mach numbers. The pressure's initial values are very high for an over-expanded nozzle than the under-expanded and ideally expanded nozzles. From the wall duct field, it is seen that the flow becomes oscillatory for lengths L = 10D to 6D owing to the collaborations of the waves, the duct wall, and the influence of the ambient pressure. The recovery of the tube pressure also gets shifted towards the downstream for the more considerable duct lengths. The flow quality with and with no flow control mechanism is identical for duct lengths 10D and 8D. Lower duct lengths show mixed trends regarding flow development, and the flow's quality is concerned. The flow control mechanism is effective once the nozzle flows with favorable pressure or at the design NPRs. When the nozzle has more pressure than ambient values, the control becomes useful, quickly raising the pressure's values.